Prospective longitudinal assessment of Albumin-to-Creatinine ratio (ACR) in a clinical cohort of people living with HIV in Gaborone, Botswana - Mosepele Mosepele; Kago Kebotsamang; Ponego Ponatshego; Kesaobaka Molebatsi; Thato Moshomo; Lucky Mokgatlhe; Shahin Lockman; Robert Gross; Joseph Jarvis; Shabbar Jaffar; Duolao Wang (BMC Infectious Diseases)
Abstract Background People living with HIV (PLWH) in sub-Saharan Africa are vulnerable to end organ dysfunction such as albuminuria, which is associated with an increased risk of cardiovascular and renal events. However, the prevalence of persistent albuminuria among PLWH in Africa is unclear. This observational prospective study assessed for persistence of albuminuria in a cohort of PLWH on longterm antiretroviral therapy (ART) across various HIV service platforms in Gaborone, Botswana. Methods A subgroup of ART treated PLWH (n = 867) from a larger cross-sectional study (n = 1537) assessing prevalence of albuminuria among PLWH at a referral hospital HIV clinic and satellite HIV clinics in Gaborone, were invited to participate in a 12-month long albuminuria prospective cohort study between January 2020 and March 2022. During three planned study visits, albumin-creatinine (ACR) was computed using urine albumin measured using immunoturbidimetric assay and urine creatinine using colorimetric assay (Jaffe method), at the Botswana Harvard HIV Reference Laboratory. ACR trajectory groups were identified using growth mixture models, and factors associated with ACR trajectory were analyzed using modified Poisson regression. Results Among the 623 adults with complete data for all 3 study visits, their baseline median age was 50 (42–57) years with a median HIV disease duration of 13.1 (8.7–16.7) years, and 266 (42.7%) of them were female. Study participants were categorized into two ACR trajectory groups: low increasing ACR, N = 290 (46.5%) and moderate increasing ACR, N = 333 (53.5%) groups. ACR increased by 4.7 mg/g in the slow increasing ACR groups versus 11.5 mg/g in the moderate increasing ACR trajectory group by end of follow-up. Active use of Tenofovir, aRR 1.27 [95% CI 1.02–1.60], p = 0.036, or ACEi/ARB, aRR 1.31 [95% CI 1.07–1.61], p = 0.008, and an elevated baseline ACR, aRR 1.34 [95% CI 1.28–1.41], p < 0.001, were all associated with being in the moderate increasing ACR trajectory group. Conclusion Chronic, treated HIV infection was associated with more than 5 fold increase in ACR over 12 months. Future studies should explore the extent to which modifiable risk factors and HIV specific factors for progressive increase in albuminuria could be aggressively controlled among PLWH.